Perencanaan dan Peningkatan Kinerja Organisasi: Tinjauan Literatur Sistematis Tentang Peran Komunikasi, Kepemimpinan, dan Motivasi dalam Efektivitas Organisasi Pendidikan - Umamul Muslikhin; Syafitri Aulia Wulandari; Riski Hidayatul Lael (Lembaga Pengembangan Kinerja Dosen, 2026)
Planning and improving the performance of educational organizations is a strategic issue that requires a managerial approach integrated with psychological aspects. This study aims to examine and synthesize factors influencing organizational performance through a management psychology approach. The method used was a qualitative systematic literature review design for scientific articles from 2022–2025 obtained from Google Scholar. Data collection techniques were carried out through documentation and article selection based on inclusion criteria, resulting in seven articles for analysis. Data analysis used a thematic approach to identify patterns and relationships between findings. The results showed that organizational performance improvement is influenced by three main factors: structured human resource planning, effective organizational communication, and transformational leadership and work motivation as psychological factors. These findings indicate that integration between structural and psychological aspects plays a crucial role in improving organizational effectiveness. In conclusion, a management approach that integrates planning and psychological factors can improve the performance of educational organizations sustainably.